2006
DOI: 10.1002/cncr.21983
|View full text |Cite
|
Sign up to set email alerts
|

The relation between hypoxia‐inducible factor (HIF)‐1α and HIF‐2α expression with anemia and outcome in surgically treated head and neck cancer

Abstract: BACKGROUND.Hypoxia promotes tumorigenesis through the hypoxia‐inducible factor (HIF) pathway. There are 2 main homologues of the regulatory proteins, HIF‐1α and HIF‐2α, which have different effects in genetic knock‐out experiments. Anemia may contribute to hypoxia by reducing oxygen delivery, but it is not known whether this influences HIF‐α expression in tumors.METHODS.The expression of HIF‐1α, HIF‐2α, carbonic anhydrase‐9 (CA‐9), and peripheral hemoglobin (Hb) levels in 151 patients who underwent surgery for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 35 publications
8
64
1
Order By: Relevance
“…In agreement with previous reports (21,33,34), we observed that HIF-1α expression was correlated with T stage, overall survival, and disease-free survival of patients with OSCC. It was suggested that rapid tumor growth results in large tumor size and hypoxic area, which thereby induces the stabilization of HIF-1α (21).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous reports (21,33,34), we observed that HIF-1α expression was correlated with T stage, overall survival, and disease-free survival of patients with OSCC. It was suggested that rapid tumor growth results in large tumor size and hypoxic area, which thereby induces the stabilization of HIF-1α (21).…”
Section: Discussionsupporting
confidence: 93%
“…Another transcription factor, Sp1, and translational factor, hypoxiainducible factor-1a, have also been implicated in regulation of VEGF expression and radiosensitivity (33). Hypoxia-induced hypoxia-inducible factor-1a may be more likely to contribute to expression of VEGF in advanced stage III/IV tumors in our series (Table 1), as Winter et al (34,35) have shown that increased hypoxia-inducible factor-1a expression is associated with stage III/IV disease in specimens of patients with HNSCC undergoing surgery. It is important to note that, of patients with higher baseline VEGF levels, 11 of 12 (92%) showed decreased longitudinal VEGF levels with treatment, consistent with our other finding that longitudinal decrease in VEGF also represents a predictor of response of oropharyngeal SCC to chemoradiation therapy.…”
Section: Discussionsupporting
confidence: 61%
“…In patients with esophageal squamous cell carcinoma, high HIF-1a expression was also associated with lymph node metastasis, serosa infiltration, tumor stage, and overall survival time in esophageal squamous cell carcinoma patients (Chai et al, 2013). HIF-1a expression was also correlated with angiogenesis and unfavorable prognosis in bladder cancer, gastrointestinal stromal tumor of the stomach, earlystage invasive cervical cancer, pancreatic cancer, head and neck cancer, nonsmall cell lung cancer, melanoma, and breast and ovarian cancers (Birner et al, 2000;Giatromanolaki et al, , 2003Koukourakis et al, 2002;Shibaji et al, 2003;Takahashi et al, 2003;Theodoropoulos et al, 2004;Winter et al, 2006;Klatte et al, 2007;Sun et al, 2007a;Daponte et al, 2008;Yamamoto et al, 2008). The above studies indicate that increased expression of HIF-1a proteins in tumor cells, whether induced by hypoxia or aberrant oncogenic signaling, is responsible for driving tumor growth and progression, most likely by regulating the expression of crucial target genes that are involved in carcinogenesis.…”
Section: Hif-1a and Cancer Prognosismentioning
confidence: 99%